A high‐performance mode multiplexer based on hybrid spoof surface plasmon polariton and substrate integrated waveguide. Issue 12 (14th October 2022) - Zhang, Xuewei; Liu, Shaobin; Zheng, Xinyuan; Liao, Kun
Abstract: In this study, a high‐performance mode multiplexer based on hybrid spoof surface plasmon polaritons and a substrate integrated waveguide (SSPP‐SIW) was investigated and experimentally demonstrated. First, we show the dispersion characteristics, eigen‐mode, and field patterns of the SSPP‐SIW unit structure and show that it can support the propagating of odd and even modes. By using different feeding technologies, the odd and even modes of the SSPP are excited simultaneously in the same waveguide structure and work in the same frequency band. Then, based on the proposed hybrid SSPP‐SIW unit, we constructed the same‐frequency mode multiplexer working in the frequency range of 5.1–8.4 GHz with isolation larger than 30 dB. The lower and upper cutoff frequencies of the passband can be independently controlled by changing the width of the SIW and trapezoid‐shaped groove design of the SSPP‐SIW unit. Finally, a prototype of the mode multiplexer was manufactured and measured. The experimental results of the fabricated sample agreed well with the simulation results, which proved the validity of the design. The proposed design combines the design of slotline SSPP, SIW, and mode composite transmission lines to achieve high isolation and high selectivity in addition to same‐frequency mode multiplexing. We believe that the proposed design a dual‐mode multiplexer with the same frequency may play an important role in improving the channel capacity in modern wireless network communication systems.